The enduring financial and monetary consequences of the us freeze : an SDR recycling proposal - Sakbani, M.M (United nations conference on trade and development, 1982)
It contains the enduring financial and monetary consequences of the us freeze : an SDR recycling proposal, towards arab monetary integration : a dynamic application of the theory of optimal currency are Brian Ames, the United Nations convention on a code of conduct for liner conferences; by Peter Faust No.11, Intra - industry trade of developing countries and some policy issues; by Refik Erzan & Samuel Laird No.12, footloose and fancy-free? : people who move as asource of income for least developed countries; by Edward Dommen No.13, regional and local government finance in the Sudan; by Nick Devas No.14, modelling fertility and mortality rates in the framework of a demographic-economic model; by Jurgen Richtering No.15, on the potential for expanding south-south trade through the extension of mutual preferences among developing countries; by Refik Erzan, Samuel Laird & Alexander Yeats No.16, export performance and output growth in developing countries; by Reinaldo Goas, external assistance to least developed countries : an anonymous country's case by I.G. Karmiloff No.4, development strategies for the 1980s: old myths and new ideas by Giovanni Andrea Cornia No.6, the influence of non-tariff barriers on exports from socialist countries of Eastern Europe; by Andrezej Olechowski & Alexander Yeats No.10, empirical review of the financial crisis in mexico, by ncalves & Jurgen Richtering No.17, the generalized system of preferences: a quantitative assesment of the direct trade effects and of policy options; by Guy Karsenty & Sam Laird No.18, unctad, structural adjustment and structural change: in search of a comprehensive approach; by Reinaldo Goncalves No.20, talking or fighting? political evolution in Rwanda and Burundi, 1998-1999, financial system and policies in Turkey in the 1980s; by Yilmaz Akyuz No.25, determinants of protection and evolving forms of North-South trade, Juan A.de Castro No.26.